A narrative review of Telehealth service success and sustainability in rural healthcare settings - Dhinagar SelgalRaddy; Muhammad Suhail Abdul Wali; Catherine Soo Shen Chan; Norhidayah Danial; Veshny Ganesan; Abdul Rahman Ramdzan; Nuurain Amirah Mohd Razi (Penerbit Universiti Malaysia Sabah, 2025)
Telehealth services have emerged as a promising solution to address healthcare disparities, improving access to care, reducing costs, and enhancing patient outcomes. This review explores the potential of telehealth in improving healthcare access, as well as the factors leading to its success and sustainability. Examining the promise and constraints of telemedicine adoption provides insights into the broader possibility and implications of telehealth technologies. A narrative review analyzed 12 English-language literatures (2019-2023) from PubMed, Science Direct, Scopus, ProQuest, and Emerald Insight, focusing on telehealth data, regulations, success factors, and rural access. Telehealth offers significant benefits, particularly in improving access to healthcare for rural and underserved populations, reducing travel time and costs, and enhancing patient engagement. It also aids in early disease detection and management, leading to better patient outcomes and reducing unnecessary hospital admissions. However, challenges remain, especially in technological infrastructure, where inadequate internet connectivity in rural areas hampers effective implementation. Patient satisfaction depends on convenience, efficiency, privacy, and communication, all of which can be compromised by technical issues. Six critical factors for telehealth success include vision, ownership, adaptability, economics, efficiency, and equipment, which must be addressed for sustainable adoption, particularly in rural settings. Despite the potential of telehealth services to revolutionize healthcare access, challenges such as funding limitations, infrastructure barriers, and concerns about the quality of telemedicine encounters persist. For telehealth services to be successful and sustainable in the long run, several issues must be resolved. Strategies include enhancing infrastructure, ensuring adherence to regulations and guidelines, and fostering awareness and acceptance among healthcare professionals and patients. The results highlight the necessity of ongoing investigation, assessment, and strategic planning to fully realize the promise of telehealth services, particularly concerning cancer treatment and other crucial areas of healthcare. Keywords: Telehealth, Healthcare Access, Rural Health, Health Technology, Sustainability in Healthcare